2018
DOI: 10.1016/j.ab.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Continuous thrombin generation in whole blood: New applications for assessing activators and inhibitors of coagulation

Abstract: Hemostatic tests have been utilized to clarify the blood coagulation potential. The novel thrombin generation (TG) assay of this study provides explicit information and is the most physiologically-relevant hemostatic test ex vivo. We describe how this assay allows for TG under a number of relevant circumstances. First, whole blood (WB) from healthy individuals was analyzed ± 5 pM tissue factor (TF) and ± contact pathway inhibition. Without an exogenous initiator TG was decreased and delayed, but addition of 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
0
19
0
2
Order By: Relevance
“…used as a pharmacodynamic marker for restoration of hemostasis for hemophilia treatment and anticoagulation reversal, although plasma thrombin generation assays do not include cellular components of whole blood,34,35 and a correlation between restoration of thrombin generation and hemostasis has not been established in bleeding patients taking FXa inhibitors. In the present study, we used pooled human plasma and the same version of TF-TG assay as F I G U R E 3 Effect of andexanet on TF-TG (ETP) in the presence of rivaroxaban or apixaban compared with 4F-PCCs.…”
mentioning
confidence: 99%
“…used as a pharmacodynamic marker for restoration of hemostasis for hemophilia treatment and anticoagulation reversal, although plasma thrombin generation assays do not include cellular components of whole blood,34,35 and a correlation between restoration of thrombin generation and hemostasis has not been established in bleeding patients taking FXa inhibitors. In the present study, we used pooled human plasma and the same version of TF-TG assay as F I G U R E 3 Effect of andexanet on TF-TG (ETP) in the presence of rivaroxaban or apixaban compared with 4F-PCCs.…”
mentioning
confidence: 99%
“…Higher TG is characterized by decreased lagtime and increased ETP and peak values, indicating a state of hypercoagulability. 8,[12][13][14] The data obtained from TGTs using low or high concentrations of TF revealed that the peripheral blood samples obtained from patients after 4 months of CVC insertion had a higher potential for TG than the samples obtained from controls and patients with 1 month of CVC insertion (Table 1).…”
Section: Tgt Parametersmentioning
confidence: 99%
“…When platelet activation occurs, a greater amount of thrombin is generated during the amplification and propagation of the coagulation cascade, resulting in an exponential increase of thrombin . Thrombin is considered the key enzyme of the coagulation system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations